2003
DOI: 10.1161/01.cir.0000051365.81920.28
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Milrinone in Preventing Low Cardiac Output Syndrome in Infants and Children After Corrective Surgery for Congenital Heart Disease

Abstract: Background-Low cardiac output syndrome (LCOS), affecting up to 25% of neonates and young children after cardiac surgery, contributes to postoperative morbidity and mortality. This study evaluated the efficacy and safety of prophylactic milrinone in pediatric patients at high risk for developing LCOS. Methods and Results-The study was a double-blind, placebo-controlled trial with 3 parallel groups (low dose, 25-g/kg bolus over 60 minutes followed by a 0.25-g/kg per min infusion for 35 hours; high dose, 75-g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
313
4
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 689 publications
(326 citation statements)
references
References 15 publications
5
313
4
4
Order By: Relevance
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 71%
See 1 more Smart Citation
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 71%
“…Longer CPB time is also repeatedly reported to be associated with prolonged mechanical ventilation following CHD surgery (17).…”
mentioning
confidence: 97%
“…In these, milrinone has been employed primarily as an inotrope and systemic vasodilator, rather than as a pulmonary vasodilator. Following cardiac surgery, milrinone appears effective in preventing low cardiac output states; however, in the preterm transitional circulation the same benefits were not observed [17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the use of high-dose milrinone after pediatric congenital heart surgery reduces the risk of LCOS [15].…”
Section: Discussionmentioning
confidence: 99%
“…Milrinone is a drug commonly used to support cardiac output after congenital heart surgery in neonates, infants, and children. Pharmacokinetic studies suggest that milrinone clearance is greater and its volume of distribution larger in children than in adults [3,15], but infants appear to have lower milrinone clearance than children [3].…”
Section: Anesthesiology and Clinical Science Issn 2049-9752mentioning
confidence: 99%